2020
DOI: 10.1038/s41598-020-76227-7
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus infection induces a non-canonical autophagy independent of the ULK and PI3K complexes

Abstract: Coxsackievirus B3 (CVB3) is a single-stranded positive RNA virus that usurps cellular machinery, including the evolutionarily anti-viral autophagy pathway, for productive infections. Despite the emergence of double-membraned autophagosome-like vesicles during CVB3 infection, very little is known about the mechanism of autophagy initiation. In this study, we investigated the role of established autophagy factors in the initiation of CVB3-induced autophagy. Using siRNA-mediated gene-silencing and CRISPR-Cas9-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…To exclude the involvement of 3CL pro , we performed in- vitro cleavage assay. Time-course treatment revealed that ULK1 was not targeted by SARS-CoV-2 3CL pro , whereas coxsackievirus 3C pro , the positive control [ 21 ], demonstrated efficient cleavage of ULK1 ( Fig. 2 D).…”
Section: Resultsmentioning
confidence: 99%
“…To exclude the involvement of 3CL pro , we performed in- vitro cleavage assay. Time-course treatment revealed that ULK1 was not targeted by SARS-CoV-2 3CL pro , whereas coxsackievirus 3C pro , the positive control [ 21 ], demonstrated efficient cleavage of ULK1 ( Fig. 2 D).…”
Section: Resultsmentioning
confidence: 99%
“…Our experiments revealed that inhibition of RIPK1, as well as inhibition of RIPK3, led to a reduction of viral replication of approximately 50%, indicating that activity of both kinases is required for viral replication. For intestinal epithelial cells, it was already shown that RIPK3 functions as a positive regulator of CVB3 replication, playing a role in regulation of autophagy, a process that is utilized by CVB3 for replication [22,38]. Although RIPK3 may be involved in the facilitation of CVB3 replication, it is nevertheless a key player of the necroptosis pathway, which may be detrimental to CVB3 replication, especially if the cells die too early before replication is successfully completed.…”
Section: Discussionmentioning
confidence: 99%
“…Cell fractionation revealed that SNAP47 and VP1 (a wellknown membrane-associated protein) were enriched on the membrane fractions (Figure 4B). Recent evidence supported the idea that CVB3-induced autophagy bypassed the requirement for canonical autophagy factors, such as the unc-51-like kinase (ULK1) and beclin-phosphatidylinositol 3-kinase (PI3K) complexes, which are crucial for basal and starvation-induced autophagy [16,17]. To test whether SNAP47 functioned as a noncanonical factor participating in CVB3-induced autophagy, we infected SNAP47-KO and WT cells with CVB3.…”
Section: Snap47 Interacts With Atg14 On the Cellular Membrane Fractions Alongside Vp1mentioning
confidence: 99%
“…However, enteroviruses (EVs), such as CVB3, have evolved to subvert this pathway for pro-viral purposes [5]. It was observed that CVB3 can induce autophagy independent of the canonical initiation complex and subsequently utilize the autophagosome membranes as scaffolds for viral replication [16,17]. CVB3 can also prevent the maturation of the autophagosome by limiting autophagosome-lysosome fusion [18,19], thereby generating very large autophagy-related structures, termed megaphagosomes [20,21].…”
Section: Introductionmentioning
confidence: 99%